Gambaran Karakteristik Etiologi dan Penyakit Penyerta Pasien End-Stage Renal Disease yang Menjalani Hemodialisis di RS Al-Islam pada Tahun 2018–2022 - Ilhan Rakha Aryawardana; Yani Triyani; Sara Puspita (Bandung Conference Series: Medical Science, 2024)
Abstract. In the last few decades there has been an increase in cases of chronic kidney disease (CKD). An increase in CKD cases can result in an increase in cases of end-stage renal disease (ESRD) which can be indicated by an increase in hemodialysis procedures every year. According to data from the Indonesian Renal Registry (IRR) in 2018, the number of new patients undergoing hemodialysis in West Java increased from the previous year by 50% (from 7,444 to 14,771 patients), based on this data, an analysis of the etiology and comorbidities of ESRD patients in 2018–2022 is needed. The aim of this study is to distributively describe the etiology and comorbidities of ESRD cases at Al-Islam Hospital in 2018–2022. The method used in this research is descriptive quantitative with a retrospective approach using the case series method. Samples were taken from medical records of new hemodialysis patients in 2018–2022 and there were 769 ESRD patients. The results of this study showed that there was an increase in ESRD patients by 20.4% during 2018–2022 with the main etiologies being hypertensive kidney disease (61.9%), diabetic nephropathy (19.5%), other causes (6.5%), primary glomerulopathy (4.6%), and lupus nephropathy (3.5%), while the main comorbidities were hypertension (57.0%), diabetes mellitus (16.3%), cardiovascular disease (6.5%), cerebrovascular disease (2.7%), and tuberculosis (2.2%). Conclusion, the most common etiologies during 2018–2022 were hypertensive kidney disease and diabetic nephropathy, while the most common comorbidities were hypertension and diabetes mellitus. From the results of this research, it is hoped that it can become a reference for establishing ESRD prevention programs and for conducting other research to deepen other characteristics using other methods. Abstrak. Dalam beberapa dekade terakhir terjadi peningkatan kasus chronic kidney disease (CKD). Peningkatan kasus CKD dapat mengakibatkan peningkatan kasus end-stage renal disease (ESRD) yang dapat diindikasikan dengan peningkatan tindakan hemodialisis setiap tahun. Menurut data Indonesia Renal Registry (IRR) tahun 2018 jumlah pasien baru yang menjalani hemodialisis di Jawa Barat meningkat dari tahun sebelumnya sebesar 50% (dari 7.444 menjadi 14.771 pasien), berdasarkan data tersebut diperlukan analisis etiologi dan penyakit penyerta pasien ESRD pada tahun 2018–2022. Tujuan penelitian ini ialah menggambarkan secara distributif etiologi dan penyakit penyerta kasus ESRD di Rumah Sakit Al-Islam pada tahun 2018–2022. Metode penelitian ini adalah deskriptif kuantitatif dengan pendekatan retrospektif menggunakan metode case series. Sampel diambil dari rekam medis pasien baru hemodialisis pada tahun 2018–2022 dan didapatkan pasien ESRD sebanyak 769 pasien. Hasil penelitian terjadi peningkatan pasien ESRD sebesar 20,4% selama tahun 2018–2022 dengan etiologi utama penyakit ginjal hipertensif (61,9%), nefropati diabetik (19,5%), penyebab lainnya (6,5%), glomerulopati primer (4,6%), dan nefropati lupus (3,5%), sementara untuk penyakit penyerta utama hipertensi (57,0%), diabetes melitus (16,3%), penyakit kardiovaskular (6,5%), penyakit serebrovaskular (2,7%), dan penyakit tuberkulosis (2,2%). Simpulan, etiologi yang paling banyak terjadi selama tahun 2018–2022 adalah penyakit ginjal hipertensif dan nefropati diabetik, sementara penyakit penyerta yang paling banyak diderita adalah hipertensi dan diabetes melitus. Berdasarkan hasil penelitian diharapkan dapat menjadi acuan untuk pembentukan program prevensi ESRD dan penelitian untuk memperdalam karakteristik lainnya menggunakan metode lain.